2018
DOI: 10.1155/2018/7865024
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Stability and Transdermal Delivery of Bioactive Compounds in Green Robusta Coffee Beans Extract Loaded Nanostructured Lipid Carriers

Abstract: e aim of this study was to develop green robusta coffee beans extract loaded nanostructured lipid carriers (NLCs) for enhancing dermal application and its efficiency. e green robusta coffee beans extract cultivated in Chumphon (CP) exhibited the highest antioxidant activity in the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay with IC 50 of 34.1 ± 0.9 µg/ml, lipid peroxidation inhibition with percentage inhibition of 38.8 ± 1.7, and ferric reducing antioxidant power (FRAP) assay with a FRAP valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
1
19
0
1
Order By: Relevance
“…In contrast, Boelzinger et al showed greater penetration of ChA from microemulsion than from the gel or emulsion [ 65 ]. However, an increase of CA penetration was observed through the pig ear after using liposomes [ 66 ] and nanostructured lipid carriers [ 67 ]. The same substances in different vehicles may penetrate deeper or accumulate in greater amounts in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Boelzinger et al showed greater penetration of ChA from microemulsion than from the gel or emulsion [ 65 ]. However, an increase of CA penetration was observed through the pig ear after using liposomes [ 66 ] and nanostructured lipid carriers [ 67 ]. The same substances in different vehicles may penetrate deeper or accumulate in greater amounts in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…14 Required HLB (rHLB) plays an important role while selecting suitable type and amount of surfactant for NLC formulation. 16 rHLB of lipids and lipid matrix is determined to calculate the amount of emulsifiers to be added in formulation. The rHLB value for lipid is the HLB value of emulsifier which is necessary for appropriate emulsification i.e.…”
Section: Surfactantsmentioning
confidence: 99%
“…The mixture is put through high pressure homogenization and analyzed for least particle size. 16,18,19 Other ingredients Organic salts and ionic polymers may be employed as counter-ions in formulation of nano structure carriers to overcome the challenge of encapsulating water soluble drug molecules. Surface-modifiers are another category of excipients used in formulation of NLC to minimize their phagocytic uptake by the macrophages in reticuloendothelial system (RES).…”
Section: Surfactantsmentioning
confidence: 99%
“…The particle size, polydispersity index (PDI), and zeta potential of unloaded NLCs were measured by Zetasizer (Zetasizer ® ZS, Malvern Instruments Ltd., UK). Each formulation was diluted at a ratio of 1:100 with deionized water and then the diluted sample was measured the particle size and polydispersity index (PDI) at room temperature (25 ± 0.5°C) with the detection angle of 173° (Nitthikan et al., 2018). The measurement was performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%